Targeted cell ablation in zebrafish using optogenetic transcriptional control - Mruk, Karen (Development, 2020)
Cell ablation is a powerful method for elucidating the contributions of individual cell populations to embryonic development and tissue regeneration. Targeted cell loss in whole organisms has been typically achieved through expression of a cytotoxic or prodrug-activating gene product in the cell type of interest. This approach depends on the availability of tissue-specific promoters, and it does not allow further spatial selectivity within the promoter-defined region(s). To address this limitation, we have used the light-inducible GAVPO transactivator in combination with two genetically encoded cell-ablation technologies: the nitroreductase/nitrofuran system and a cytotoxic variant of the M2 ion channel. Our studies establish ablative methods that provide the tissue specificity afforded by cis-regulatory elements and the conditionality of optogenetics. Our studies also demonstrate differences between the nitroreductase and M2 systems that influence their efficacies for specific applications. Using this integrative approach, we have ablated cells in zebrafish embryos with both spatial and temporal control.